Organization of scientific-cognitive independent work of the students of philological faculty in the context of humanistic oriented education (Pedagogy of Higher and Secondary Education, 2013)
Bondar L. A. Organization of scientific-cognitive independent work of the students of philological faculty in the context of humanistic oriented education.This paper proposes an innovative approach to considering scientific and cognitive independent work of students – philologists taking into account the up-to-date statuses of the modern philosophical methodology of cognizing complex systems, processes, phenomena – synergies and changes, which occur in contemporary philosophical anthropological paradigm, refracted in pedagogical theory and practice.
Keywords: scientific-cognitive independent work; a synergistic approach; humanistic oriented training